Management of hip fracture patients on direct oral anticoagulants: a survey of orthopaedic trauma surgeons, systematic review, and meta-analysis - Clay Spitler, MD; Robert Rutz, MD; Nigel Blackwood, MD; Meghan Wally, PhD; Joseph Johnson, MD; Peter Krause, MD; Jaimo Ahn, MD; Zuhair Mohammed, BS; Mark McClure, MD; Rebecca Billings, MLS; Ziqing Yu, PhD; Matthew Yeager, BA; et al. (OTA International, 2025)
Abstract. Objectives:. This systematic review examined the literature regarding management of fracture patients who take direct oral anticoagulant (DOAC) medications, with a focus on delay in surgical treatment, and need for transfusions. In addition, a survey of orthopaedic trauma surgeons was conducted to gain insight on current practices. Data Sources:. A review of PubMed, Cochrane, Embase, and Scopus databases was performed from inception through March 2024, including English language publications. Study Selection:. Studies were included if they reported time to surgery and transfusion rates among fracture patents who were taking DOAC medications. Additional data points were collected on an “if-reported” basis, including mortality, venous thromboembolism, and bleeding complications. Data Extraction:. In all, 4546 abstracts were screened. Full-text review was conducted on 86 publications, and 25 articles were included in the final analysis. Each article was independently screened by 2 reviewers, with disputes settled by a third reviewer. Study quality was assessed using the Methodological Index for Non-Randomized Studies (MINORS) tool. Data Synthesis:. Descriptive statistics are reported for overall study findings. Meta-analysis was performed for the variables “time to surgery” and “transfusion rate.” Conclusions:. Our findings indicate that fracture patients taking DOACs experience longer delays before surgery but have equivalent transfusion rates compared with nonanticoagulated patients. Survey results indicate that surgeons do not delay operating on emergent or percutaneous cases, regardless of anticoagulant medications. In circumstances when they do delay, they are more likely to do so for patients taking DOAC medications. Level of Evidence:. Level III, systematic review and meta-analysis of Level II and III articles.